Flocculation of copper(II) and tetracycline from water using a novel pH- and temperature-responsive flocculants. (December 2015) - Yang, Zhen; Jia, Shuying; Zhuo, Ning; Yang, Weiben; Wang, Yuping
Graphical abstract: The mechanism of flocculation of copper(II) and TC using a pH- and temperature-responsive flocculant. Highlights: A dual (pH- and thermal-) responsive flocculant (CND) is employed for the first time. The flocculant shows high efficiency for coremoval of copper(II) and tetracycline. Pairwise interactions among CND, copper(II) and TC exist in bridging flocculation. Application fields of flocculation in treating livestock wastewaters were extended. A new approach for concentrated treatment of industrial wastewater was provided. Abstract: Insufficient research is available on flocculation of combined pollutants of heavy metals and antibiotics, which widely exist in livestock wastewaters. Aiming at solving difficulties in flocculation of this sort of combined pollution, a novel pH- and temperature-responsive biomass-based flocculant, carboxymethyl chitosan- graft -poly( N -isoproyl acrylamide- co -diallyl dimethyl ammonium chloride) (denoted as CND) with two responsive switches [lower critical solution temperature (LCST) and isoelectric point (IEP)], was designed and synthesized. Its flocculation performance at different temperatures and pHs was evaluated using copper(II) and tetracycline (TC) as model contaminants. CND exhibited high efficiency for coremoval of both contaminants, whereas two commercial flocculants (polyaluminum chloride and polyacrylamide) did not. Especially, flocculation performance of the dual-responsive flocculant under conditions of temperature > LCST and IEP(contaminants)<pH < IEP(CND) was much better than that under other conditions. Further investigation on flocculation mechanism via pH monitoring, zeta potential measurements, floc properties analyses and spectral characterization indicated that, pairwise interactions among CND, copper(II) and TC were present in bridging flocculation, including charge attraction, coordination and hydrophobic effect. Based on these pairwise interactions, copper(II) and TC exerted "aid" roles to each other's removal with the existence of CND, and preferable flocculation performance was thus achieved.